Answers

  • Brainly User
2014-09-17T11:10:18+05:30
Join A to mid-point of BC at D. Hence ED = BE = (1/4)BC --(1)
In triangle AED, AE² = AD² + ED² -----------------(2)
In triangle ABD, AD²  = AB² - BD²   --------------(3)
Putting value of AD² from (3) into (2),
AE² = AB² - BD² + ED² = AB² - (BC/2)² + (BC/4)²
as BD = (1/2)BC and ED = (1/4)BC from (1).

OR AE² = AB² - (AB/2)² + (AB/4)² as BC = AB as triangle ABC is equilateral.

Simplifying this , 16AE² = 13AB²
0
2014-09-17T11:25:55+05:30
See the attachment for sort proof-----.>
0